PENGGUNAAN CAMERA TRAP DALAM MENGIDENTIFIKASI SATWA LIAR DI HUTAN MALAGUFUK DISTRIK MAKBON KABUPATEN SORONG - Turot, Amatus; Serkadifat, Yetti S; Boger, Imanuel T.F (LPPM Politeknik Saint Paul Sorong, 2024)
The Malagufuk Forest is known as an area outside the conservation area that has high biodiversity. This can be proven by the opening of the area as an ecotourism area, especially for bird observation. But that doesn't mean that other animals other than birds can't be found. It's just that other wildlife is sometimes difficult to find. To find out the existence of this hard-to-find wildlife, it is necessary to use a trap camera, so that it is more efficient to make observations. Based on this, the author feels the need to use trap cameras to identify wildlife in the Malagufuk forest, Sorong Regency. The purpose of writing this thesis is to find out how to use trap cameras and the types of wild animalsthat have been found using trap cameras inMalagufuk District, Sorong Regency. Data collection took place starting in September 2021 in the Malagufuk forest, Sorong Regency. Data collection was carried out using 6 trap cameras for 7 days. The results of the study showed that therewas a research location using a trap camera and 4 types of wildlife were found, namely mambruk birds, maleo, wild boars, lau-lau and ground rats.